2010
DOI: 10.1007/s00246-010-9781-y
|View full text |Cite|
|
Sign up to set email alerts
|

Successful Emergent Coronary Thrombolysis in a Neonate with Kawasaki’s Disease

Abstract: This report describes the case of a 29-day-old infant with Kawasaki's disease who presented in extremis with multiple coronary aneurysms and coronary thromboses, myocardial ischemia, and congestive heart failure. The infant successfully underwent emergent coronary thrombolysis with tissue plasminogen activator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Our literature search revealed only a few reported cases of suspected NKD worldwide (18 cases, including 14 English literature and 4 Chinese literature) (Table 1) [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], together with this case, 19 cases in total. In all the presented cases including ours, 12 were male and 7 were female, the age of onset was 1-26 days.…”
Section: Discussionmentioning
confidence: 99%
“…Our literature search revealed only a few reported cases of suspected NKD worldwide (18 cases, including 14 English literature and 4 Chinese literature) (Table 1) [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], together with this case, 19 cases in total. In all the presented cases including ours, 12 were male and 7 were female, the age of onset was 1-26 days.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombolytic agents such as urokinase and rT-PA have been used to treat acute myocardial ischemia secondary to thrombus formation in CAAs of patients with KD [5,10,14]. Improved outcome was reported when the agents were administered directly into the coronary arteries [5,15].…”
Section: Discussionmentioning
confidence: 99%
“…Ariyoshi et al [4] reported three cases, in patients aged 20-35 years, in whom primary percutaneous coronary interventions in combination with intracoronary thrombolysis proved to be safe and effective in acute myocardial infarction. Karia et al [14] reported a 29-day-old child with KD who presented with multiple medium-size CAAs as well as coronary thromboses, myocardial ischemia, and congestive heart failure. The infant successfully underwent intracoronary infusion of rT-PA.…”
Section: Discussionmentioning
confidence: 99%
“…Kawasaki disease (KD) is a self-limiting systemic vasculitis of unknown etiology that typically occurs in children aged between 6 months and 5 years [1]. It is much less common under 3 months of age and extraordinarily rare in the neonatal period [2][3][4][5][6][7][8]. A 12-year Japanese nationwide survey reported only 23 cases of neonatal KD [2], while only about 10 neonatal cases have been reported in other countries in the English-language literature [4].…”
Section: Introductionmentioning
confidence: 99%